1994
DOI: 10.1177/039139889401700908
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventricular support using pulsatile Abiomed BVS 5000 and centrifugal Biomedicus-pump in postcardiotomy shock

Abstract: Since we started using ventricular assist devices (VAD) in July 1987 up to August 1993, 63 of 15,650 (0.4%) patients (pts) who underwent open heart surgery were supported postoperatively by VAD at out institution. Forty-three were male and 20 female, mean age 55.5 years. In 49 pts coronary artery bypass grafting (CABG), in 8 pts valve surgery, in 3 pts combined CABG and valve surgery and in 3 pts corrective procedures for congenital heart disease were performed. Perioperative myocardial infarction was the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Others report the treatment of PGF with LVAD [9,18] or with BVAD [16,17,19,20]. On the basis of an evaluation of more than 200 cases with MCS in our hospital [2,4,5,6,7] the advantages and disadvantages of the individual systems could be proven. The indications for the individual pumps were deduced from these data.…”
Section: Discussionmentioning
confidence: 92%
“…Others report the treatment of PGF with LVAD [9,18] or with BVAD [16,17,19,20]. On the basis of an evaluation of more than 200 cases with MCS in our hospital [2,4,5,6,7] the advantages and disadvantages of the individual systems could be proven. The indications for the individual pumps were deduced from these data.…”
Section: Discussionmentioning
confidence: 92%
“…In the posttransplant group, three of six (50%) patients were weaned and two (33%) were successfully discharged home. Various investigators have reported encouraging results in this group, with wean rates ranging between 47% and 100%, and discharge rates between 20% and 71% (16)(17)(18)(19)(20). The available knowledge emphasizes the recoverability of ventricular function in the transplanted heart during primary graft failure or severe acute rejection with cardiogenic shock.…”
Section: Discussionmentioning
confidence: 96%
“…The BioMedicus Centrifugal Pump (BCP) (Medtronic BioMedicus, Eden Prairie, MN) is a constant-speed, nonpulsatile device that can be used in children of all ages [53][54][55]. This pump is often used without a membrane oxygenator, establishing a different modality from traditional ECMO, and as such will be reviewed separately.…”
Section: Available Devicesmentioning
confidence: 99%